A Study on the Glucose Breath Test Positivity Rate and Occurrence of Small Intestine Bacterial Overgrowth-Related Symptoms Caused by Long-Term Use of Proton Pump Inhibitor (PPI) Versus Potassium-Competitive Acid Blocker (P-CAB) in Elderly Patients - Na Rae Lim; Saenal Lim; Woo Chul Chung (Advances in Pharmacological and Pharmaceutical Sciences)
Conclusion: Long-term use of gastric acid suppressants resulted in positive GBT in approximately 30% of patients, and the risk was particularly high in elderly patients. The occurrence of SIBO-related symptoms was significant in long-term use of PPIs and in patients with positive GBT.